Association of Six Complex Inflammatory Indicators with Prognosis in Patients with Intravenous Thrombolysis Stroke - Li Y; Xi L; Sun H; Yu F; Liang Q; Qie T; Dai B (International Journal of General Medicine)
Yinglei Li,1,* Lingyun Xi,2,* Haichuan Sun,1 Feifei Yu,1 Qing Liang,1 Tao Qie,1 Bing Dai1 1Department of Emergency Medicine, Baoding NO.1 Central Hospital, Baoding, People’s Republic of China; 2Department of Laboratory and Pathology, The Hospital of 82nd Group Army PLA, Baoding, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bing Dai, Department of Emergency Medicine, Baoding NO.1 Central Hospital, Baoding, People’s Republic of China, Email 447023235@qq.comObjective: The objective of this study is to examine the correlation between neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), systemic immune inflammation index (SII), systemic inflammation response index (SIRI) and pan-immune-inflammation value (PIV) with the outcome following 3 months of thrombolysis in individuals diagnosed with acute ischemic stroke.Methods: A retrospective analysis was conducted on a cohort of 762 patients who received intravenous thrombolysis between January 2019 and December 2022. The values of NLR, PLR, LMR, SII, SIRI and PIV were calculated based on relevant blood indices obtained upon admission. Logistic regression analysis using R software was employed to examine the correlation between SIRI, SII, PIV, and poor prognosis following 3 months of thrombolysis, with their distribution analyzed across the study population and various outcomes. Receiver operating characteristic (ROC) curves were utilized to analyze and evaluate their predictive efficacy for adverse outcomes.Results: The unfavorable prognosis group exhibited significant differences from the favorable prognosis group in various hematological markers, including PLR, NLR, LMR, SII, SIRI, and PIV, as indicated by ROC values of 0.613 (95% confidence interval (CI), 0.564– 0.661), 0.707 (95% CI, 0.663– 0.751), 0.614 (95% CI, 0.567– 0.662), 0.715 (95% CI, 672– 0.758), 0.631 (95% CI, 0.584– 0.679), and 0.569 (95% CI, 0.520– 0.619) respectively. (4) Conclusions: PLR, NLR, LMR, SII, SIRI, and PIV demonstrated associations with adverse outcomes at the 3-month mark in patients who underwent intravenous thrombolysis, with NLR (ROC is 0.707) and SII (ROC is 0.715) showing the most pronounced significance and PIV (ROC is 0.569) exhibiting the least significance.Keywords: acute ischemic stroke, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, systemic immune inflammation index, systemic inflammation response index